Clinical case of multiple sclerosis associating with persistent herpes virus infection: dynamics on the background of antiviral and immunocorrective treatment - Davydova, T (Annals of Mechnikov's Institute, 2019)
Rationale: Multiple sclerosis (MS) is a chronic inflammatory disorder of the central nervous system. Infectious triggers of MS are being actively investigated. Substantial evidence supports the involvement of the Epstein-Barr virus (EBV), though other viruses, bacteria, protists, and fungi are also being considered. For many years, researchers have discussed the relationship of demyelinating processes and development of multiple sclerosis (MS) associated with the activation and persistence of herpes viruses. In recent years, studies have increasingly proved the pathogenetic role herpes viruses in the development of this disease, but this requires further study. There is growing evidence that viruses can play a role by acting as external triggers. However, it is not known, one virus is the cause MS or several viruses can act as an impulse to the development the disease. Clinical case: Patient N., female, 35 years old, was diagnosed with multiple sclerosis, disseminated, relapsing remitting, exacerbation stage with moderately expressed right-sided paraparesis, with motor and sphincter disorders, pronounced vestibule-ataxic (vestibulocerebellar) syndrome, cognitive impairment, EDSS 4.5–5.0 in 2013. A brain and spine MRI showed numerous bilateral hyperintense (17) T1, and several (5) T2 lesions and FLAIR contrast-enhancing over the hemispheres and cerebellum and several (6) T1, (4) T2 lesion in her cervical spinal cord sizes from 0.3 cm to 1.1x0.6x1.1 cm individual foci with signs of perifocal edema. At the time of diagnosis complaints of dizziness, shakiness when walking, weakness and a feeling of numbness in the limbs, discoordination of movements, impaired urination by the type of delay with frequent urges, decreased performance, fatigue, unstable gait, muscle cramps, decreased muscle strength (4), slight speech disturbances, depression and anxiety. She treated with pulses of corticosteroids (1.5 g methylprednisolone) and plasmapheresis with gradual tapering of the steroids over a period of 4 weeks according to standard treatment protocols in the neurological department Kharkiv Regional Clinical Hospital. The first symptoms appeared 6 months before the diagnosis was established and gradually increased. Complaints were preceded by an episode of acute viral infection and prolonged low-grade fever for 3 months. We consider the clinical case patient with MS, it was detection the abnormalities in the immune status and viral load (herpes type 4 – Epstein-Barr virus, EBV and human herpes virus 6 – HH6), and positive dynamics was observed in condition of patient and MRI data after antiviral and immunocorrective therapy. Interventions: We administered valacyclovirum as the first therapy in combination with recombinant interferons α2b and cridanimodum. Additionally was recommended high doses of vitamins. Outcomes: The patient's condition improved after treatment: EDSS 3.0–3.5. MRI also showed positive dynamics: several small lesions in the brain disappeared, large MS lesions became smaller in size. (11) T1, and several (5) T2 over the hemispheres and cerebellum and FLAIR contrast-enhancing and several (4) T1, (3) T2 lesion in her cervical spinal cord sizes from 0.3 cm to 0.7x0.4x0.8 cm individual foci without signs of perifocal edema. Conclusion: Early diagnosis and active antiviral and immunocorrective therapy is important when herpes are detecting in MS patients for treating and preventing further development of the disease, so we would like to highlight some aspects of the therapy carried out in this case for the perspective planning relevant clinical studies in the similar direction.